The Effect of Yellow Natural Color from Turmeric on Physical and Sensory Properties of Arenga Starch-Taro (Colocasia esculanta L.) Flour Noodle - Rahayu, Ervika; Ariani, Dini; Miftakhussolikhah, Miftakhussolikhah; Elfanti, Maharani P.; Pranoto, Yudi (Indonesian Journal of Natural Pigments, 2019)
Arenga starch-taro (Colocasia esculanta L.) flour noodle is an alternative carbohydrate source made from 75% arenga starch and 25% taro flour. This research purpose is to know the effect of natural color extracts on the physical and sensory properties of noodle. Coloring extraction was done using 5 variances of turmeric rhizome (0.06; 0.12; 0.18; 0.24; and 0.30 g (fresh weight/ml water). Then, noodle was made and physical and sensory properties were evaluated. The result showed that coloring extracts addition decreased the break compression, elongation, and tensile strength of arenga starch-taro flour sohun. Turmeric rhizome extract addition increased the yellow color.